BIOGRAFI DAN PEMIKIRAN DR. H. ABDULLAH AHMAD, LATAR BELAKANG BERDIRI DAN PERKEMBANGAN SERTA RUH / FILOSOFI LEMBAGA PENDIDIKAN SUMATERA THAWALIB, ADABIYAH, PGAI DAN SEBARAN SEKOLAH-SEKOLAH SUMATERA THAWALIB - Fitra, Joni Darma; Prima, Ari; Syaifullah, Syaifullah; Asmaret, Desi; Julhadi, Julhadi (STKIP Pesisir Selatan, 2025)
Sheikh Abdullah Ahmad changed the traditional teaching system with a religious school system (Madrasah) named Adabiah School. This naming may be intended as a symbol of the revival of science in Islamic civilization and inspired by the hadith of the Prophet Muhammad SAW narrated by Al-Asykari. This study examines in depth the biography and thoughts of DR.H. Abdullah Ahmad as a cleric, journalist, and intellectual from Padang Panjang, West Sumatra. He is known as a pioneer of modern Islamic education in Indonesia. The background of the establishment and development and spirit / philosophy of the educational institutions of Sumatera Thawalib, Adabiyah and PGAI, as well as the distribution of Sumatera Thawalib schools. With a historical and epistemological approach, this paper explores the roots of Abdullah Ahmad's thoughts in the context of the pioneers of Islamic Education, his interaction with modernity, and his contributions to the education, social, and da'wah systems. This paper was written to fulfill the assignment as a doctoral student in the Islamic Studies program, in the Islamic Education and Law Course from a historical, social and political perspective.